INVESTIGATIONS ON STRUCTURAL INFLUENCE ON FRICTION FACTOR OF MULTI-COMPONENT VACUUM- PLASMA COATING - S. A. Ivashchenko; I. A. Ivanou; S. A. Sultan; Kh. T. Karmaji (Наука и техника, 2006)
It is revealed that under relatively low values of the accelerating potential Ubasic = 0-100 B) metal - silicon - nitrogen coating formation occurs when chemical reactions of nitride formation are absent An increase of the Ubasic value up to -(150-250) В leads to higher nitrogen concentration in the area of the crystallization, that changes thermodynamic conditions of coating grains’ growth and contributes to the nitrogen enriched stratum isolation in the form of streaks. Technological gas (nitrogen or argon) pressure increase promotes a roughness growth of the precipitated coating surfaces. It is determined that the best friction properties of the coatings have been obtained with friction along the hardened steel 40X. While using more ductile material as a rider (unhardened steel 45) the friction factor growth is observed. The instrumental coating ZrSiN precipitated with the Ubasic value -150B and having a layer structure is characterized by the least and most stable value of the friction factor (0.22 with friction along the unhardened steel 45 and 0.2 along the hardened steel 40X).